PERSAINGAN ANTAR PENGENDARA GO-JEK ONLINE DI KOTA PEKANBARU - Syam, Dedy Setiawan; ", Syamsulbahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study answers about the types of transportation services Gojek online in the city of Pekanbaru has developed, ranging from the services of Go-ride, Go-send, Go-mart, Go-shop and Go-message, while other Go-jek services such as Go-bak, Go-med and Go-busway have not developed in accordance with the needs of consumers or customers of Pekanbaru City residents. Forms of competition that occur between Gojek riders in Pekanbaru City in addition to the availability of vehicles that are healthy, economical, safe and comfortable for consumers, have good relationships or also determine the success of gaining profit coffers, either through online applications or no. In fact, the effort of an ojek driver to foster good relations with customers or consumers to carry out various Gojek services, also greatly determines the increase in Gojek's income in the future, especially if Gojek drivers are able to provide various facilities in all service matters service to customers or consumers. Meanwhile, the contradictory relationship that occurs between online application-based Gojek riders in Pekanbaru City only takes place in terms of attempts to vilify other parties or other Gojek riders by providing unfavorable information to customers, such as accusations of being less safe and comfortable and not Guaranteed passenger safety and behavior of Gojek drivers who are naughty to hang out at intersections or crossroads to search for customers or consumers manually (offline) without using applications that have been set by the company. Keywords: Competition, Contravention and Go-jek Online